The adaptive features of cardiohemodynamic and gas exchange readjustment under test load in young northern natives of different generations - I. V. Averyanova; A. L. Maksimov (Сибирский научный медицинский журнал, 2023)
The research aimed to study the restructuring of hemodynamics, gas exchange, and heart rate variability parameters in response to the stress test with breathing in confined space in different generations of young Caucasoid natives permanently residing in Russia’s Magadan region. Material and methods. Two hundred 18–21 year old male migrants and those born to them in 1–3 generations, all Caucasians by origin, participated in the Magadan city survey. During the resting and confined space rebreathing sessions we registered subjective heart rate, blood pressure, oxygen and carbon dioxide level. The heart rate variability was recorded by the Varicard complex coupled with the Iskim-6 software. The exhaled gas level was determined by the Karbonik analyzer. The blood oxygen saturation was measured by a pulse oximeter. An electronic tonometer was used for the blood pressure control. Results and discussion. Both resting and rebreathing tests revealed lower HRV rates in the group of migrants (zero generation): not only did they exhibit a decrease in the activity of the autonomic regulation contour – they also reported an imbalance in the sympathetic and parasympathetic regulation of cardiac hemodynamics. However, the 3rd generation subjects showed an optimal and stable balance between the links of autonomic regulation, both at rest and during functional exercise with rebreathing, which is reflected in the parameters of arterial pressure and gas exchange. Interestingly, the most informative indicators of adaptation are not the absolute values of the studied indicators but the difference between their background and testing values, which to a greater extent hold information on the body functional reserves of those born in the North in different generations constantly living in the extreme conditions of the North. It was found that the increase in parasympathetic activity and its influence on the cardiac rhythm both at rest and in response to a breathing test was most pronounced in the group of natives of the 3rd generation, which reflects a deeper degree of their adaptation to the northern conditions. Apparently, this is a manifestation of the general strategy of functional restructuring of the body’s regulatory systems aimed at the formation of optimal compensatory-adaptive restructuring of gas homeostasis during an increased period of residence in the North.